2012
DOI: 10.1111/j.1654-109x.2012.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐variation between plant above‐ground biomass and phenology in sub‐alpine grasslands

Abstract: Question: Resources quality and quantity are both important determinants of habitat use for large herbivores. We aim to understand how these two variables vary throughout the growing season in sub-alpine grasslands. How do productivity and phenology (quality) of different plant communities within a landscape vary over time? Do productivity and phenology co-vary? Which environmental constraints or growth form composition best explain differences in productivity and phenology among plant communities?Location: Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Rhododendron ferrugineum and Vaccinium sp. ), mountain hay meadows, and screes (Duparc et al 2013). In this site, chamois have no natural predators and are not in sympatry with other wild ungulates (Darmon et al 2014).…”
Section: French Study Sitementioning
confidence: 97%
“…Rhododendron ferrugineum and Vaccinium sp. ), mountain hay meadows, and screes (Duparc et al 2013). In this site, chamois have no natural predators and are not in sympatry with other wild ungulates (Darmon et al 2014).…”
Section: French Study Sitementioning
confidence: 97%
“…Chamois are at a high density in subalpine pastures and lower density in forests (Redjadj 2010). Mouflon overlap with chamois in spring and summer in alpine pastures (Darmon et al 2012) and shift to forest during November when snow comes (Duparc et al 2012). Roe deer mostly use forests (Redjadj 2010;Redjadj et al 2014).…”
Section: Study Site and Organismsmentioning
confidence: 98%
“…This would indicate that the same biophysical factors that drive the timing that grasslands start their growth (e.g., snow cover, temperature, precipitation) also dictate the seasonal magnitude of biomass and quality [66]. Among these biophysical factors, we speculate that prolonged snow cover is primarily responsible for this co-variation because it delays the timing of growth and promotes forage biomass and quality by increasing the nitrogen content of soils and protecting grasses from early season freeze events [66,67]. Duparc et al [66] similarly found that more productive grasslands reached their peak in forage later in the season than less productive grasslands in the French Alps.…”
Section: Spatiotemporal Variation In Grassland Biomass and Quality Acmentioning
confidence: 99%